On Validity of the Gharânîq Hadîth: Examining the Religious Reason of Exegesis Literatures - Arif, Mahmud; Kurjum, Mohammad (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
It is interesting to re-discuss the controversy about something claimed as a prophetic tradition (al-HadÃ®th), especially when it is related to its explanatory-doctrinal function to al-Qurâ€™Ã¢n and to its implication for essential Islamic doctrines. The account of GharÃ¢niq claimed by some experts as a prophetic tradition is one of the models of old cases, but it remains to produce a religious discourse colored with pros and cons. Some experts believe in the existence and validity of the account of GharÃ¢niq, some others reject it partly or with â€œnotesâ€, and the others reject it totally. This article tries to analyze critically the account of GharÃ¢niq by exploring literatures on exegesis and traditions in order to discuss and treat this topic more proportionally.